Comparison of VIDAS and Radioimmunoassay Methods for Measurement of Cortisol Concentration in Bovine Serum. (28th October 2013) - Proverbio, Daniela; Perego, Roberta; Spada, Eva; Bagnagatti de Giorgi, Giada; Belloli, Angelo; Pravettoni, Davide
Abstract : Radioimmunoassay (RIA) is the "gold standard" method for evaluation of serum cortisol concentration. The VIDAS cortisol test is an enzyme-linked fluorescent assay designed for the MiniVidas system. The aim of this study was to compare the VIDAS method with RIA for measurement of bovine serum cortisol concentration. Cortisol concentrations were evaluated in 40 cows using both VIDAS and RIA methods, the latter as the reference method. A paired Student's t -test, Pearson's correlation analysis, Bland-Altman plot, and Deming regression analysis were used to compare the two methods. There was no statistically significant difference between mean serum cortisol concentrations measured by VIDAS or RIA methods (P = 0.6570 ). Both methods were able to detect significant differences in mean low and high cortisol concentrations (P < 0.00014 RIA and P < 0.0016 VIDAS). The correlation coefficient was low, but a Bland-Altman plot and Deming regression analysis show neither constant nor proportional error. The VIDAS method produced slightly higher values than RIA, but the difference was small and in no case did the mean value move the normal range. Results suggest that VIDAS method is suitable for the determination of bovine serum cortisol concentration in studies of large numbers of animals.